Kurz vor dem Untergang, oder doch nicht? Ein Blick auf den Stamm Benjamin als mehrfach schwindende Gemeinschaft - KLEIN, Johannes (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
Benjamin is the youngest of twelve brothers; King Saul calls his tribe the smallest in Israel. Geographically, the tribe is in the midst of all Israel, on the border of north and south, often fiercely contested and overall very influential. From these observations, the author attempts to draw lessons for the minority to which he belongs, namely the Transylvanian Saxons, which is also a small, perhaps soon dwindling community, but nevertheless at least still also successful. Are the commonalities signs that one is on the verge of extinction, or will it be possible to pull oneself together once more? Possibilities of strategies that can make survival possible are hinted at, for example, building bridges while taking one's own identity into account, participating in the structures of power, adapting and pursuing realpolitik, rejecting any kind of fanaticism, especially religious fanaticism, if necessary striving for external assimilation in order to preserve the most important values. Nevertheless, it is pointed out that the topic still needs interdisciplinary research.